Improving the Nutritional Values of Cassava Pulp through Supplementation of Selected Leaves Meal and Fermentation with Chrysonilia Crassa - Sugiharto, Sugiharto; Widiastuti, Endang; Yudiarti, Turrini; Wahyuni, Hanny Indrat; Sartono, Tri Agus (ANIMAL PRODUCTION, 2021)
This study evaluated the impact of fermentation with Chrysonilia crassa on nutritional composition and antioxidative activity of the mixture of cassava pulp and selected leaves meal. Cassava pulp (60 g) was mixed thoroughly with 35 g leaves meal of either cassava, M. Oleifera, or L. leucocephala, and inoculated with Chrysonilia crassa starter (5 g). The mixture was aerobically incubated for 3 days at room temperature and analyzed for the proximate composition, gross energy, true protein, antioxidant activity, and amino acid content. The fermented products showed higher crude protein, ether extract, ash, and gross energy but lower fibre content than unfermented cassava pulp. Both leaves meal supplementation and fermentation increased the true protein content of cassava pulp. Superior antioxidant activities and higher amino acids were observed in the fermented products than raw cassava pulp. In conclusion, supplementation of leaves meal in conjunction with Chrysonilia crassa-fermentation improved the nutritional values and antioxidant potential of cassava pulp.